Signal and backgrounds for leptoquarks at the CERN LHC. II. Vector leptoquarks - Belyaev, A. [UNESP]; Éboli, O. J P [UNESP]; Funchal, R. Z.; Lungov, T. L. [UNESP] (American Physical Society (APS), 1999)
We perform a detailed analyses of the CERN Large Hadron Collider (LHC) capability to discover first generation vector leptoquarks through their pair production. We study the leptoquark signals and backgrounds that give rise to final states containing a pair e+e- and jets. Our results show that the LHC will be able to discover vector leptoquarks with masses up to 1.8-2.3 TeV depending on their couplings to fermions and gluons. ©1999 The American Physical Society.